Influence of material orientation, loading angle, and single-shot repetition of laser shock peening on surface roughness properties - Lebea, Lebogang; Desai, Dawood; Ngwangwa, Harry; Nemavhola, Fulufhelo (Frontiers in Manufacturing Technology, 2024)
Titanium alloy Ti6Al4V is extensively utilized in biomedical applications due to its excellent biocompatibility, corrosion resistance, and mechanical properties. The design of dental implant surface textures has changed throughout time to address issues with oral rehabilitation in both healthy and damaged bones. The longevity of an implant is significantly impacted by surface roughness. This study examines the use of laser shock peening (LSP) as a surface modification technique to improve the mechanical properties of implants. The purpose of the study is to develop surface roughness parameters using computational methods a such studies have not yet been contemplated. The single shot angle, shot repeat, time, material orientation, and laser power are applied for the first time simultaneously to evaluate the impact of material orientation and loading angles on surface roughness parameters. The study showed that the developed computational model's compressive residual stress was -578.45 MPa, while the experimental samples were -592.18 MPa. Consequently, the difference between the computational and experimental results was 2.32%. Without regard to material orientation or angle, the compressive residual stress of the samples under examination was found to be -578.450 MPa after three repetitions and to decreased to -1.620 MPa after four. These results demonstrate that by varying the material orientation and loading angle, the Ra value may be increased four times.